Ocular tuberculosis: an update - Sharma, A; Thapa, B; Lavaju, P (Nepalese Journal of Ophthalmology, 2011)
Tuberculosis (TB) is an infectious disease responsible for significant morbidity and mortality worldwide. It is a resurgent disease in the developed world. The World Health Organization estimates that one third of the world’s population is currently infected, with 9 million new cases occurring annually, leading to 3 million deaths per year (WHO Report, 2007). The disease affects the ocular anterior segment, the posterior segment, and adnexa. The purpose of this review is to describe the ocular manifestations, diagnosis and treatment of tuberculosis and to emphasize the fact that ocular tuberculosis may occur in the absence of systemic clinical activity and may mimic several clinical entities. Various studies have shown a clinical significance of purified protein derivative test results and computerized tomography of the chest while, molecular diagnostic procedures have provided a new approach to establishing the diagnosis of ocular tuberculosis. The current review focuses on the diagnostic modalities, various clinical features, and treatments for management of intraocular tuberculosis recommended in recent publications. It is an update on the manifestations and management of ocular tuberculosis. Keywords: tuberculosis; uveitis; choroiditis; granuloma; Mantoux Skin Test; Interferon-g release assays; anti tubercular treatment DOI: 10.3126/nepjoph.v3i1.4280Nepal J Ophthalmol 2011;3(5):52-67